Binary copolymer with adjustable low critical solution temperature and viscosity-temperature characteristics and preparation method thereof

By preparing a dual polymer composed of N-isopropyymamidide and acrylic hydroxylxerne, the existing temperature-sensitive polymers' lack of temperature response and viscous temperature characteristics are solved. The adjustable low critical dissolution temperature and efficient heating and thickening effect are suitable for the development of high -temperature oil fields, and have the advantages of environmental protection and low cost.

CN116444721BActive Publication Date: 2025-01-28CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310365603.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-07
Publication Date
2025-01-28
Estimated Expiration
2043-04-07

AI Technical Summary

Technical Problem

The existing temperature-sensitive polymer oil flooding agents have shortcomings in temperature response regulation capabilities and viscosity-temperature characteristics, especially in the development of high-temperature oil fields.

Method used

A binary cluster is composed of N-isopropyramine and acrylic hydroxyl butne. It is prepared through the free radical polymerization reaction, and the organic film is separated and purified. Solk temperature.

Benefits of technology

The low critical dissolution temperature of the dual -co -concentration is achieved and the high -efficiency viscous temperature characteristics can be significantly increased and thickened at a lower concentration. It is suitable for the development of high -temperature oil fields. The use of organic solvents has environmental protection and low -cost advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004166640400000021
    Figure BDA0004166640400000021
  • Figure BDA0004166640400000022
    Figure BDA0004166640400000022
  • Figure BDA0004166640400000081
    Figure BDA0004166640400000081
Patent Text Reader

Abstract

The present invention belongs to the field of petrochemical technology, and specifically relates to a binary copolymer with adjustable lower critical solution temperature and viscosity-temperature characteristics and a preparation method thereof. With N-isopropyl methacrylamide and hydroxybutyl acrylate as polymerization monomers, potassium persulfate as initiator, heating in an aqueous solution to initiate a free radical polymerization reaction, after the reaction is completed, the residual initiator, polymerization monomer and oligomer are removed by organic membrane separation to obtain a binary copolymer concentrate, and then the binary copolymer solid powder is obtained by freeze drying. The binary copolymer prepared by the present invention can be obtained by adjusting the ratio of N-isopropyl methacrylamide and hydroxybutyl acrylate to obtain a binary copolymer with different lower critical solution temperatures. When the concentration of the copolymer in the aqueous solution is higher than 1%, it has a significant warming and thickening effect, and has potential application value in the field of chemical oil displacement agents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petrochemical industry, and in particular relates to a binary copolymer with adjustable low critical solution temperature and viscosity-temperature characteristics and a preparation method thereof. Background Art

[0002] Chemical flooding refers to adding certain chemical additives to the water injected into the reservoir to change the properties of the displacement fluid and the interface properties between the displacement fluid and crude oil to improve the recovery rate. Chemical flooding mainly includes surfactant flooding, polymer flooding, alkali flooding and composite flooding. Among them, polymer-based flooding agents are a new type of flooding agent developed in recent years, and temperature-sensitive polymer flooding agents are of special significance for the development of high-temperature oil fields.

[0003] The thermosensitive polymer oil displacement agents reported so far have shown great potential, but there are still many problems, such as insufficient temperature response adjustment ability, and the viscosity-temperature characteristics can only be effectively reflected under high polymer concentration conditions. Therefore, it is urgent to develop thermosensitive polymer oil displacement agents with adjustable temperature responsiveness and efficient viscosity-temperature characteristics. Summary of the invention

[0004] One of the objects of the present invention is to provide a binary copolymer having an adjustable low critical solution temperature and efficient viscosity-temperature characteristics.

[0005] To achieve this purpose, the present invention adopts the following technical solutions:

[0006] A thermosensitive binary copolymer, the general structural formula of which is shown in (Ⅰ).

[0007]

[0008] Among them, X is 0.75 to 0.85, and Y is 0.15 to 0.25.

[0009] Another object of the present invention is to provide a method for preparing the compound of formula (I), wherein the preparation reaction formula of the compound of formula (I) is as follows:

[0010]

[0011] The preparation method of the compound of formula (I) is carried out according to the following steps:

[0012] With N-isopropyl methacrylamide and hydroxybutyl acrylate as polymerization monomers and potassium persulfate as initiator, a free radical polymerization reaction is initiated in an aqueous solution heated to 80°C under a nitrogen atmosphere. After the reaction is completed, the residual initiator, polymerization monomer and oligomer are removed by organic membrane separation to obtain a binary copolymer concentrate, and then the binary copolymer solid powder is obtained by freeze-drying.

[0013] The molar ratio of N-isopropyl methacrylamide to hydroxybutyl acrylate is 4:1-4, the mass of potassium persulfate is 1-3% of the mass of N-isopropyl methacrylamide, the reaction time is 4-24 hours, and the molecular weight cutoff range of the organic membrane is 500-3500Da.

[0014] The lower critical solution temperature of the binary copolymer is between 35°C and 52°C.

[0015] The binary copolymer is used as a chemical oil displacement agent.

[0016] The advantages of the present invention are that the lower critical solution temperature of the binary copolymer provided by the present invention can be regulated by adjusting the ratio of the polymerization units N-isopropyl methacrylamide and hydroxybutyl acrylate, and the binary copolymer provided by the present invention has a significant temperature-raising and thickening effect when the concentration is as low as 1%. In addition, the copolymer prepared by the present invention through organic membrane separation and purification avoids the use of organic solvents, and therefore has the advantages of being green, environmentally friendly and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The hydrogen nuclear magnetic resonance spectra of the binary copolymers prepared in Examples 1 to 4 of the present invention are shown.

[0018] Figure 2 This is the infrared spectra of the binary copolymers prepared in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0019] The method of the present invention is further described below in conjunction with specific embodiments.

[0020] Example 1 Preparation of binary copolymer

[0021] 1.27 g of N-isopropyl methacrylamide and 0.36 g of hydroxybutyl acrylate were dissolved in 100 mL of ultrapure water, and 30 mg of potassium persulfate was added. The reaction system was evacuated by a water pump for 5 minutes, and then replaced with nitrogen. After repeating 5 times, the reaction system was heated to 80° C. under a nitrogen atmosphere and stirred for 6 hours. The reaction solution was cooled to room temperature, purified and concentrated by organic membrane separation (molecular weight cutoff 3500 Da), and freeze-dried to obtain a white solid (yield 89%).

[0022] The prepared binary copolymers were characterized by hydrogen nuclear magnetic resonance spectroscopy. Figure 1. The hydrogen NMR spectrum showed the methyl hydrogen signal (chemical shift ~1) on the isopropyl group in the polymerized unit N-isopropylmethacrylamide and the two methylene hydrogen signals (chemical shift ~1.5) between the butyl groups in hydroxybutyl acrylate, indicating the successful preparation of the binary copolymer. The molar fractions of the polymerized units N-isopropylmethacrylamide and hydroxybutyl acrylate in the copolymer were calculated by hydrogen NMR spectrum to be 0.85 and 0.15, respectively, indicating that the copolymer is composed of polymerized units N-isopropylmethacrylamide and hydroxybutyl acrylate in a molar ratio of 0.85:0.15. The infrared spectrum of the prepared binary copolymer is shown in Figure 2 The ester bond C=O stretching vibration peak (~1725cm -1 ) and amide bond C=O stretching vibration peak (~1640cm -1 ), further indicating the successful preparation of the binary copolymer.

[0023] Example 2 Preparation of binary copolymer

[0024] 1.27 g of N-isopropyl methacrylamide and 0.72 g of hydroxybutyl acrylate were dissolved in 100 mL of ultrapure water, and 30 mg of potassium persulfate was added. The reaction system was evacuated by a water pump for 5 minutes, and then replaced with nitrogen. After repeating 5 times, the reaction system was heated to 80° C. under a nitrogen atmosphere and stirred for 10 hours. The reaction solution was cooled to room temperature, purified and concentrated by organic membrane separation (molecular weight cutoff 2000 Da), and freeze-dried to obtain a white solid (yield 87%).

[0025] The prepared binary copolymers were characterized by hydrogen nuclear magnetic resonance spectroscopy. Figure 1 The hydrogen NMR spectrum showed the methyl hydrogen signal (chemical shift ~1) on the isopropyl group in the polymerized unit N-isopropylmethacrylamide and the two methylene hydrogen signals (chemical shift ~1.5) between the butyl groups in hydroxybutyl acrylate, indicating the successful preparation of the binary copolymer. The molar fractions of the polymerized units N-isopropylmethacrylamide and hydroxybutyl acrylate in the copolymer were calculated by hydrogen NMR spectrum to be 0.80 and 0.20, respectively, indicating that the copolymer is composed of polymerized units N-isopropylmethacrylamide and hydroxybutyl acrylate in a molar ratio of 0.80:0.20. The infrared spectrum of the prepared binary copolymer is shown in Figure 2 The ester bond C=O stretching vibration peak (~1725cm -1 ) and amide bond C=O stretching vibration peak (~1640cm -1 ), further indicating the successful preparation of the binary copolymer.

[0026] Example 3 Preparation of binary copolymer

[0027] 1.27 g of N-isopropyl methacrylamide and 1.08 g of hydroxybutyl acrylate were dissolved in 100 mL of ultrapure water, and 30 mg of potassium persulfate was added. The reaction system was evacuated by a water pump for 5 minutes, and then replaced with nitrogen. After repeating 5 times, the reaction system was heated to 80° C. under a nitrogen atmosphere and stirred for 20 hours. The reaction solution was cooled to room temperature, purified and concentrated by organic membrane separation (molecular weight cutoff 1000 Da), and freeze-dried to obtain a white solid (yield 84%).

[0028] The prepared binary copolymers were characterized by hydrogen nuclear magnetic resonance spectroscopy. Figure 1 The hydrogen NMR spectrum showed the methyl hydrogen signal (chemical shift ~1) on the isopropyl group in the polymerized unit N-isopropylmethacrylamide and the two methylene hydrogen signals (chemical shift ~1.5) between the butyl groups in hydroxybutyl acrylate, indicating the successful preparation of the binary copolymer. The molar fractions of the polymerized units N-isopropylmethacrylamide and hydroxybutyl acrylate in the copolymer were calculated by hydrogen NMR spectrum to be 0.78 and 0.22, respectively, indicating that the copolymer is composed of polymerized units N-isopropylmethacrylamide and hydroxybutyl acrylate in a molar ratio of 0.78:0.22. The infrared spectrum of the prepared binary copolymer is shown in Figure 2 The ester bond C=O stretching vibration peak (~1725cm -1 ) and amide bond C=O stretching vibration peak (~1640cm -1 ), further indicating the successful preparation of the binary copolymer.

[0029] Example 4 Preparation of binary copolymer

[0030] 1.27 g of N-isopropyl methacrylamide and 1.44 g of hydroxybutyl acrylate were dissolved in 100 mL of ultrapure water, and 30 mg of potassium persulfate was added. The reaction system was evacuated by a water pump for 5 minutes, and then replaced with nitrogen. After repeating 5 times, the reaction system was heated to 80° C. under a nitrogen atmosphere and stirred for 24 hours. The reaction solution was cooled to room temperature, purified and concentrated by organic membrane separation (molecular weight cutoff 800 Da), and freeze-dried to obtain a white solid (yield 78%).

[0031] The prepared binary copolymers were characterized by hydrogen nuclear magnetic resonance spectroscopy. Figure 1The hydrogen NMR spectrum showed the methyl hydrogen signal (chemical shift ~1) on the isopropyl group in the polymerized unit N-isopropylmethacrylamide and the two methylene hydrogen signals (chemical shift ~1.5) between the butyl groups in hydroxybutyl acrylate, indicating the successful preparation of the binary copolymer. The molar fractions of the polymerized units N-isopropylmethacrylamide and hydroxybutyl acrylate in the copolymer were calculated by hydrogen NMR spectrum to be 0.75 and 0.25, respectively, indicating that the copolymer is composed of polymerized units N-isopropylmethacrylamide and hydroxybutyl acrylate in a molar ratio of 0.75:0.25. The infrared spectrum of the prepared binary copolymer is shown in Figure 2 The ester bond C=O stretching vibration peak (~1725cm -1 ) and amide bond C=O stretching vibration peak (~1640cm -1 ), further indicating the successful preparation of the binary copolymer.

[0032] Example 5 Preparation of binary copolymer

[0033] 1.27 g of N-isopropyl methacrylamide and 1.44 g of hydroxybutyl acrylate were dissolved in 100 mL of ultrapure water, and 10 mg of potassium persulfate was added. The reaction system was evacuated by a water pump for 5 minutes, and then replaced with nitrogen. After repeating 5 times, the reaction system was heated to 80° C. under a nitrogen atmosphere and stirred for 24 hours. The reaction solution was cooled to room temperature, purified and concentrated by organic membrane separation (molecular weight cutoff 800 Da), and freeze-dried to obtain a white solid (yield 56%).

[0034] Comparative Example 1 Preparation of binary copolymer

[0035] 1.27 g of N-isopropyl methacrylamide and 2.16 g of hydroxybutyl acrylate were dissolved in 100 mL of ultrapure water, and 30 mg of potassium persulfate was added. The reaction system was evacuated by a water pump for 5 minutes, and then replaced with nitrogen. After repeating 5 times, the reaction system was heated to 80° C. under a nitrogen atmosphere and stirred for 24 hours. The reaction solution was cooled to room temperature, purified and concentrated by organic membrane separation (molecular weight cutoff 800 Da), and freeze-dried to obtain a white solid (yield 26%).

[0036] Comparative Example 2 Preparation of binary copolymer

[0037] 1.27 g of N-isopropyl methacrylamide and 1.16 g of hydroxyethyl acrylate were dissolved in 100 mL of ultrapure water, 30 mg of potassium persulfate was added, the reaction system was evacuated by a water pump for 5 minutes, and then the nitrogen was replaced. After repeating 5 times, the reaction system was heated to 80° C. under a nitrogen atmosphere and stirred for reaction for 24 hours. The reaction solution was cooled to room temperature, purified and concentrated by organic membrane separation (molecular weight cutoff 800 Da), and freeze-dried to obtain a white solid with a molar ratio of polymerization units of N-isopropyl methacrylamide and hydroxyethyl acrylate of 0.74:0.26 (yield 82%).

[0038] Example 6 Determination of lower critical solution temperature

[0039] The binary copolymer samples prepared in Examples 1 to 4 and Comparative Example 2 were formulated into 0.5% aqueous solutions by mass, and the absorbance at 650nm was measured with a UV-visible spectrophotometer as a function of temperature. The temperature at which the transmittance dropped significantly was defined as the lower critical solution temperature of the copolymer.

[0040] As shown in Table 1, the lower critical solution temperatures of the binary copolymers prepared in Examples 1 to 4 and Comparative Example 2 are 35, 40, 43, 52, and 55°C, respectively, indicating that the lower critical solution temperature of the binary copolymers prepared increases with the increase in the molar ratio of hydroxybutyl acrylate in the polymerized units in the copolymers, and when hydroxybutyl acrylate is replaced by hydroxyethyl acrylate, the lower critical solution temperature increases slightly. The above results indicate that by adjusting the molar ratio of the polymerized units in the prepared binary copolymers, thermosensitive binary copolymers with different lower critical solution temperatures can be prepared.

[0041] Table 1. Lower critical solution temperature of binary copolymers prepared in Examples 1 to 4 and Comparative Example 2

[0042] Molar ratio of polymer units in copolymer Lower critical solution temperature / ℃ Example 1: 0.85: 0.15 35 Example 2: 0.80: 0.20 40 Example 3: 0.78: 0.22 43 Example 4: 0.75: 0.25 52 Comparative Example 2: 0.74: 0.26 55

[0043] Example 9: Determination of viscosity-temperature characteristics

[0044] The binary copolymer samples prepared in Example 2, Example 4 and Comparative Example 2 were respectively prepared into aqueous solutions with mass fractions of 0.5%, 1%, 2% and 3%, and the changes in solution viscosity with temperature were measured by a digital rotational viscometer.

[0045] As shown in Table 2 and Table 3, when the mass concentration of the binary copolymers prepared in Example 2 and Example 4 is 0.5%, the solution viscosity does not change significantly with temperature, but when the mass concentration is higher than 1%, when the temperature rises to its lower critical solution temperature, the solution viscosity increases significantly, indicating that the binary copolymers prepared in Example 2 and Example 4 have a significant temperature-increasing thickening effect when the mass concentration is higher than 1%. As shown in Table 4, the binary copolymer prepared in Comparative Example 2 has a significant temperature-increasing thickening effect only when the mass concentration is higher than 2% and the temperature rises to its lower critical solution temperature, and under the condition of being higher than the lower critical solution temperature, the solution viscosity of the binary copolymer prepared in Comparative Example 2 is lower than that of the copolymer prepared in Example 4, indicating that the copolymer prepared with hydroxybutyl acrylate can achieve a more effective temperature-increasing thickening effect at a lower concentration than the copolymer prepared with hydroxyethyl acrylate.

[0046] Table 2. Viscosity of the binary copolymer prepared in Example 2 at different concentrations and temperatures

[0047]

[0048] Table 3. Viscosity of the binary copolymer prepared in Example 4 at different concentrations and temperatures

[0049]

[0050] Table 4. Viscosity of binary copolymer prepared in Comparative Example 2 at different concentrations and temperatures

[0051]

[0052]

Claims

1. A binary copolymer having adjustable lower critical solution temperature and viscosity-temperature characteristics, characterized in that: The general structural formula of the binary copolymer is shown in (I): Among them, X is 0.75 to 0.85, and Y is 0.15 to 0.

25.

2. The binary copolymer with adjustable lower critical solution temperature and viscosity-temperature characteristics according to claim 1, characterized in that: The lower critical solution temperature of the binary copolymer is between 35°C and 52°C.

3. A method for preparing a binary copolymer having adjustable lower critical solution temperature and viscosity-temperature characteristics according to claim 1, characterized in that: The preparation method comprises the following steps: using N-isopropyl methacrylamide and hydroxybutyl acrylate as polymerization monomers and potassium persulfate as initiator, heating in an aqueous solution under a nitrogen atmosphere to initiate a free radical polymerization reaction; after the reaction is completed, removing the residual initiator, polymerization monomers and oligomers through organic membrane separation to obtain a binary copolymer concentrate; and then freeze-drying to obtain a binary copolymer solid powder.

4. The method for preparing a binary copolymer having adjustable lower critical solution temperature and viscosity-temperature characteristics according to claim 3, characterized in that: The molar ratio of N-isopropylmethacrylamide to hydroxybutyl acrylate is 4:1-4.

5. The method for preparing a binary copolymer having adjustable lower critical solution temperature and viscosity-temperature characteristics according to claim 3, characterized in that: The mass of potassium persulfate is 1-3% of the mass of N-isopropylmethacrylamide.

6. The method for preparing a binary copolymer having adjustable lower critical solution temperature and viscosity-temperature characteristics according to claim 3, characterized in that: The polymerization reaction temperature is 80°C and the reaction time is 4 to 24 hours.

7. The method for preparing a binary copolymer having adjustable lower critical solution temperature and viscosity-temperature characteristics according to claim 3, characterized in that: The molecular weight cut-off range of the organic membrane is 500~3500Da.

8. The use of the binary copolymer with adjustable lower critical solution temperature and viscosity-temperature characteristics according to claim 1, characterized in that: The binary copolymer is used as a chemical oil displacing agent.

Citation Information

Patent Citations

  • Temperature-sensitive type finishing agent as well as preparation method and applications thereof

    CN101994253A

  • LCST-adjustable aggregation-induced emission hyperbranched polymer and preparation method and application thereof

    CN112920420A